Emotional Intelligence of the Head of Madrasah in Increasing Teacher Loyality - Irwansyah (Asian Journal of Applied Education (AJAE), 2022)
This study aims to describe the emotional intelligence of MTsN 1 Aceh Tengah principals in increasing teacher loyalty. the research method used is descriptive qualitative method. Data collection is done by observation and interviews. Then the data were analyzed using qualitative analysis with data collection steps, 2) data condensation, 3) data display, and 4) conclusion drawing/verifying. The results of the research show that the head of MTsN 1 Aceh Tangah has emotional intelligence with three indicators, the first is self-awareness, the second is being able to read other people's feelings in this case the feelings of subordinates namely teachers and staff, the third is social awareness, the fourth is managing relationships. With these four indicators it can be concluded that the head of MTsN 1 Aceh Tengah has emotional intelligence.